Community Empowerment in the Middle of the Covid-19 Pandemic through Pawon Urip and Management Waste Bank - Cahyaningati, Retno; Paramita, Ratna Wijayanti Daniar; Ana, Selvia Roos; Wiyono, Mokhamad Wimbo (IMPOWERMENT SOCIETY, 2022)
The existence of Covid 19 has paralyzed the world economy, including several MSME businesses out of business. The existence of Large-Scale Social Restrictions (PSBB) requires people to stay at home. To overcome problems in the food sector in the midst of the Covid-19 pandemic, the Lumajang Regency PKK Mobilizing Team initiated the formation of the Pawon Urip Program. The purpose of this Community Service Activity is to support the Pawon Urip TP-PKK Lumajang Regency Program to improve food sufficiency and community welfare. Activities carried out in this Community Service include, firstly, providing training and assistance in plant cultivation. Second, optimizing the management of the Waste Bank. Thirdly, training and mentoring on the utilization of used cooking oil waste into goods of sale value in the form of biodiesel. Community Service activities have been running smoothly. This activity certainly provides great benefits to the community, from here the community can carry out plant cultivation well, knowledge of Waste Bank management is increasing so that they can do simple bookkeeping, even saving and buying and selling waste has become the culture of the local community. Furthermore, the community can also produce biodiesel independently, as a more economical and efficient substitute.